The burden of diabetes on the soft tissue seal surrounding the dental implants - Zhang, Zhanwei; Ji, Chonghao; Wang, Daobin; Wang, Maoshan; Song, Dawei; Xu, Xin; Zhang, Dongjiao (Frontiers in Physiology, 2023)
Soft tissue seal around implant prostheses is considered the primary barrier against adverse external stimuli and is a critical factor in maintaining dental implants' stability. Soft tissue seal is formed mainly by the adhesion of epithelial tissue and fibrous connective tissue to the transmembrane portion of the implant. Type 2 diabetes mellitus (T2DM) is one of the risk factors for peri-implant inflammation, and peri-implant disease may be triggered by dysfunction of the soft tissue barrier around dental implants. This is increasingly considered a promising target for disease treatment and management. However, many studies have demonstrated that pathogenic bacterial infestation, gingival immune inflammation, overactive matrix metalloproteinases (MMPs), impaired wound healing processes and excessive oxidative stress may trigger poor peri-implant soft tissue sealing, which may be more severe in the T2DM state. This article reviews the structure of peri-implant soft tissue seal, peri-implant disease and treatment, and moderating mechanisms of impaired soft tissue seal around implants due to T2DM to inform the development of treatment strategies for dental implants in patients with dental defects.